Analisis Pengaruh Motivasi Kerja Dan Budaya Organisasi Terhadap Komitmen Kerja Karyawan Di UMKM Sektor Kreatif (Studi Pada Karyawan Kopi Kenangan di Kota Malang) - Awalyah, Azizah; Khalikussabir, Khalikussabir; Suharto, M. Khoirul Anwarudin Broto (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract Companies, including Micro, Small, and Medium-Sized Enterprises (MSMEs), must constantly improve due to the business world's rapid expansion. Human resources are a critical component of a sustainable and growing organization. The purpose of this study is to describe work motivation, organizational culture, and employee commitment. It also looks at how work motivation and organizational culture partially and simultaneously affect employee commitment in MSMEs in the creative sector, specifically among Kopi Kenangan employees in Malang City. 75 employees serve as both the population and the sample in this study, which uses a quantitative approach and survey method. A total sampling strategy is used. After passing tests for validity, reliability, normalcy, multicollinearity, and heteroscedasticity, the data were gathered via questionnaires and subjected to multiple linear regression analysis.A regression coefficient value of 1.032 supports the primary findings, which show that work motivation has a positive and significant partial effect on employee commitment. Similarly, with a regression coefficient value of 0.745, organizational culture likewise has a positive and substantial partial effect on employee commitment. Employee commitment is significantly impacted by both organizational culture and job motivation at the same time, with an F-calculated value of 120.715 that is higher than the F-table value of 2.73 and a significance value of 0.000 < 0.05.With a coefficient of determination (R2) of 0.735, job motivation and organizational culture account for 73.5% of the variation in employee commitment, with other factors outside the research model accounting for the remaining 26.5%. In conclusion, organizational culture and work motivation are critical elements that greatly increase employee engagement in MSMEs in the creative industry. Keywords: Work motivation, Organizational culture, Employee commitment, MSMEs